OPTIMIZATION STUDIES ON POST BLENDING OF CRUDE PALM AND RUBBER SEED OIL FATTY ACID METHYL ESTERS - SHAH BOKHARI, SYED AWAIS ALI (2014)
In avoiding the major issues of fossil fuel depletion and the environmental concerns, biodiesel is one of the most feasible sources of alternative energy. Rubber seeds, due to its non-edible characteristics have a potential to be converted to biodiesel. Its utilization will help to resolve food versus fuel controversy. Malaysia has a vast number of palm and rubber plantations that can supply sufficient seeds for biodiesel production. In present work, parametric studies and optimized conditions were determined via response surface methodology (RSM), using the central composite design (CCD) of the Design Expert 8.0 software. The parameters studied for solvent extraction of rubber seeds were solvent to seed ratio, temperature, extraction time and drying time of the seeds. A parametric study was also conducted to determine the effect of alcohol to oil (A:0) ratio, catalyst loading, reaction time and temperature on acid esterification and base transesterification process.